RESEARCH ACTIVITY OF STUDENTS IN THE APPLICATION OF LASER PROCESSING AND 3D PRINTING TECHNOLOGIES IN TEXTILE FABRICS - Mežinska, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Nowadays education and research promote interdisciplinary cooperation and development. An interdisciplinary approach creates change and new opportunities for design education in general, while innovation, the use of advanced materials and technologies transforms design technology studies. These changes affect the development of design technology as an integrated interdisciplinary direction, the creation of innovative solutions, products and services in research design activities. This process is facilitated by research grant projects involving students and researchers. The performed experimental research in Rezekne Academy of Technologies (RTA) engineering research centres shows the possibilities of laser processing and 3D printing in textile fabrics design, promotes innovative technological solutions in product design and ensures the development of scientifically based results. The aim of the research is to improve students' independent research activities in purposeful project activities by interacting with various engineering research centers. Research methods used: theoretical - literature and Internet resource research and analysis, empirical - action (case study) research. Eight students of engineering/design study programs and four lecturers – researchers - participants of grant projects - participate in the research. Research period 2017–2020. The research has a practical significance, because it substantiates the interdisciplinary experimental research activity process and results, determining of students' independent research activity improvement direction, promotes the transfer of research results into practice.